Teaching Strategy for Catholic Religious Education Teachers in Class XI Multiple Intelligence-Based Learning at Budi Murni 2 Medan Catholic Private Senior High School - Thomas N. Tarigan; Mimpin Sembiring; Triska Juveni Br Sembiring; Ermina Waruwu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to answer problems regarding implementation teaching strategy for catholic religious education teachers in class XI multiple intelligence-based learning at Budi Murni 2 Medan Catholic Private Senior High School.This study uses a descriptive qualitative approach. The subjects of this study are students of Class XI Budi Murni 2 Medan Catholic Private Senior High School. The informants specified in this study are 12 people consisting of catholic religious education students and teachers. The research is conducted during March and April 2023. Data analysis is carried out by reduction, display, and triangulation. The results of the study show that catholic religious education teachers at Budi Murni 2 Medan Catholic Private Senior High School have implemented appropriate teaching strategies in learning based on multiple intelligences. The suggestion of this research is that multiple intelligences can be used as a focus of teaching strategies for catholic religious education teachers in multiple intelligences-based learning at Budi Murni 2 Medan Catholic Private Senior High School